Extremely low-dose ACTH step-up protocol for West syndrome: Maximum therapeutic effect with minimal side effects - Oguni, Hirokazu; Yanagaki, Shigeru; Hayashi, Kitami; Imai, Kaoru; Funatsuka, Makoto; Kishi, Takayuki; Osawa, Makiko (Brain & development, 2006)
We studied the effectiveness of our new ACTH treatment strategy for West syndrome (WS), which was based on the results of our previous extremely low-dose ACTH study. The subjects were 31 infants with WS (cryptogenic WS in nine; symptomatic WS in 22). Synthetic ACTH-Z in a dose of 0.005 mg (=0.2 IU)/kg/day was injected once every morning for at least 2 weeks, up to a maximum of 3 weeks. When this first treatment course achieved full seizure and EEG control, ACTH was tapered to zero over the subsequent 1 or 2 weeks. In the absence of a documented response, the dosage was increased to 0.025 mg (=1.0 IU)/kg/day for the next 2 weeks (second treatment course). We analyzed the short-term as well as long-term effects, and the incidence of side effects. The first treatment course successfully controlled both spasms and hypsarrhythmia in 17 patients (55%), only spasms in one, and hypsarrhythmia in two. The second treatment course was then introduced in eight of the remaining 14 patients, providing complete suppression of WS in an additional two patients. Regarding the long-term effects, 13 patients (48%), with excellent short-term results and a longer than 1-year follow-up, remained seizure-free. Side effects of a mild degree were seen in 13 patients during ACTH treatment. Our new ACTH step-up method brought 61 and 48% of the patients into short-term and long-term remission, respectively, without significant side effects. The dose of ACTH required to control WS appears to be unexpectedly smaller than the dose we previously used.